Respon Pakcoy (Brassica rapa L.) Terhadap Pupuk Organik Cair Limbah Tahu dan Kompos Biochar - Alfred Siprianus Seran; Deseriana Bria; Natalia Desy Djata Ndua; Magdalena Sunarty Pareira; Hyldegardis Naisali (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
This study aims to determine the effect of interaction between liquid organic fertilizer from waste and biochar compost on the growth and yield of pak choi plants. This study used a Factorial Completely Randomized Design consisting of two factors. The first factor is tofu waste POC (T) while the second factor is biochar compost (K). The first factor consists of 3 levels, namely T1 = 0 ml/L of water, T2 = 100 ml/L of water, and T3 = 300 ml/L of water. The second factor consists of 3 levels, namely K1 = soil, K2 = 10% biochar compost and K3 = 30% biochar compost, so that there are 9 combinations then repeated 3 times so that there are 27 experimental units. The observed parameters include plant height, number of leaves, fresh plant weight, fresh root weight, dry plant weight, dry root weight, root length, root volume. Based on the results of the study, it showed that there was no interaction between the treatment factors of tofu waste POC and biochar compost in all parameters. In the single treatment, tofu waste POC had a significant effect on the parameters of the number of leaves, fresh weight of the crown, dry weight of the crown and dry weight of the roots. The single treatment of biochar compost had a significant effect on the parameter of the number of leaves.